(untitled) (Global Journal of Medical Research, 2014)
Foster Kennedy syndrome (FKS) is a very rare neurological syndrome with a unique ophthalmological manifestation described in 1911 by Robert Foster Kennedy attributed to anterior fossa mass lesion and raised intracranial pressure (ICP) caused by the tumor’s mass effect. Meningioma is the most common cause of the syndrome. Rarely vascular lesions and tuberculous meningitis had been reported as a cause of FKS. Here we present a case of Foster Kennedy-like syndrome, in which meningioma compressed one optic nerve and cerebral venous sinus thrombosis impair cerebral venous drainage inducing intracranial hypertension, and papilledema in the other eye. This case emphasis the importance of considering of CVST as underlying pathogenesis of raised ICP in absence of cerebral edema or obstructed hydrocephalus.